From forest to plantation: a brief history of the rubber tree - Suryanarayanan, T. S.; Azevedo, Joao Lucio [UNESP] (Indian Natl Science Acad, 2023)
This article describes how the rubber tree (Hevea brasiliensis) (Willd. ex A. Juss.) (Mull. Arg., family-Euphorbiaceae) which grows wildly in the Amazon forests, came under global focus due to industrial revolution. From 1860 to 1913, since the tree was found only in the Amazon forest, the entire world depended on a few business magnates of that region for rubber. These rubber barons enslaved many local people to extract rubber from the wildly growing trees in the forest since the efforts to grow rubber as plantations failed mainly due to a devastating fungal disease. The rubber slaves recruited to collect rubber latex from the wildly growing trees in the forest went through untold misery. The economy of towns in the Amazonas such as Manaus and Belem, which were located strategically for exporting the extracted rubber by ships, boomed. This monopoly of Amazon's rubber trade crashed due to the British which itself is an intriguing story. The 'travel' of the rubber tree from the Amazon forest to the then Southeast British colonies to be grown as plantations encompasses many fields including biology, sociology, industry, economics and environment.
Keywords: Amazonia; Charles goodyear; Hevea brasiliensis; Henry Wickham; South American leaf blight disease